2021
DOI: 10.1101/2021.01.21.427610
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Emergence of XDR high-riskPseudomonas aeruginosaST309 in South America: a global comparative genomic analysis

Abstract: Pseudomonas aeruginosa has been considered one of the major nosocomial pathogens associated with elevated morbidity and mortality worldwide. Outbreaks have been associated with few high-risk pandemic P. aeruginosa lineages, presenting a remarkable antimicrobial resistance. However, the biological features involved with the persistence and spread of such lineages among clinical settings remain to be unravel. This study reports the emergence of the ST309 P. aeruginosa lineage in South America/Brazil, more precis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…This operon encodes a T4P with two main known isoforms [94], had 14 genes on pEK204, and is a virulence factor for P. aeruginosa [95][96]. A ten-gene pil operon is involved in conjugation of pathogenicity island PAPI-1 in P. aeruginosa PA14 independently of pEK204 [95] that has been linked to P. aeruginosa ST309 infection outbreaks [97], and pil genes form part of an integrative conjugative element Pac_ICE1 in P. syringae pv actinidiae [98]. Notably, pil may be more associated with aqueous environments, and the loss of pil genes from PAPI-1 has been associated with better acute human lung [99] and mouse gut [100] infection, perhaps due to Pil proteins acting as cell surface antigens [101].…”
Section: Discussionmentioning
confidence: 99%
“…This operon encodes a T4P with two main known isoforms [94], had 14 genes on pEK204, and is a virulence factor for P. aeruginosa [95][96]. A ten-gene pil operon is involved in conjugation of pathogenicity island PAPI-1 in P. aeruginosa PA14 independently of pEK204 [95] that has been linked to P. aeruginosa ST309 infection outbreaks [97], and pil genes form part of an integrative conjugative element Pac_ICE1 in P. syringae pv actinidiae [98]. Notably, pil may be more associated with aqueous environments, and the loss of pil genes from PAPI-1 has been associated with better acute human lung [99] and mouse gut [100] infection, perhaps due to Pil proteins acting as cell surface antigens [101].…”
Section: Discussionmentioning
confidence: 99%
“…Extensively drug-resistant Pseudomonas aeruginosa ST-309 has been reported as an emerging high-risk healthcare-associated pathogen. (2,6,9). After case review, no epidemiological links were identified between the cases, despite being closely related.…”
Section: The Studymentioning
confidence: 99%